Enhancing Junior High School Students’ System Thinking Competency through Water Treatment with Plant Modification: A Focus on Environmental Pollution - Mariah Syifa Salsabila; Yayan Sanjaya; Eliyawati Eliyawati; Witsanu Suttiwan (Journal of Science Learning, 2024)
The research on the ability to think in systems in education is also minimal, which is why the ability to think in systems in Indonesia has not been optimally trained. Dealing with a system's complexity can be challenging at any age, particularly for students who must apply the system's cognitive capabilities during the learning process. Systems thinking is a key to Education for Sustainable Development (ESD) competency since it can help learners understand the complexity and dynamics of the world. This research investigates the impact of system thinking on Junior High School students through simple science projects addressing environmental pollution. The study involved 7th-grade students in a private school in Bandung, utilizing a quantitative approach with a one-group pre-test and post-test design; the research aimed to measure the improvement in students' system thinking competency using test items and analyzed the data with SPSS software and Rasch Stacking and Racking. Results from the Wilcoxon test indicated a significant difference after completing learning activities, with a 50% improvement based on Rasch analysis. This underscored the critical role of project-based learning in enhancing system thinking competency. Applying appropriate learning models is expected to enhance students' system thinking competency. The recommendation for future reference to other studies, such as directing the scientific investigation in detail. Design more precisely from the initial stage to the final stage so that the expected learning can be achieved, and students can go through all stages of STEM learning correctly to create a better prototype.